2021
DOI: 10.1108/jfrc-08-2020-0074
|View full text |Cite
|
Sign up to set email alerts
|

Has financial inclusion made the financial sector riskier?

Abstract: Purpose This paper aims to examine whether high levels of financial inclusion is associated with greater financial risk. Design/methodology/approach The study uses regression methodology to estimate the effect of financial inclusion on financial risk. Findings The findings reveal that higher account ownership is associated with greater financial risk through high non-performing loans and high-cost inefficiency in the financial sector of developed countries, advanced countries and transition economies. Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 54 publications
0
22
0
1
Order By: Relevance
“…The two financial inclusion variables used in this study are considered to be financial access indicators, namely, ATMs per 100,000 adults and bank branch per 100,000 adults. These two indicators have been widely used as measures of financial access and measures of financial inclusion by several studies in the literature such as Neaime and Gaysset (2018), Emara and El Said (2021) and Ozili (2021). The legal system quality indicators are the enforcing contracts index, strength of legal rights index, resolving insolvency index, strength of insolvency framework index and time to resolving insolvency index.…”
Section: Variable Descriptionmentioning
confidence: 99%
“…The two financial inclusion variables used in this study are considered to be financial access indicators, namely, ATMs per 100,000 adults and bank branch per 100,000 adults. These two indicators have been widely used as measures of financial access and measures of financial inclusion by several studies in the literature such as Neaime and Gaysset (2018), Emara and El Said (2021) and Ozili (2021). The legal system quality indicators are the enforcing contracts index, strength of legal rights index, resolving insolvency index, strength of insolvency framework index and time to resolving insolvency index.…”
Section: Variable Descriptionmentioning
confidence: 99%
“…They found that increased lending to small and medium-sized enterprises (SMEs) reduced the size of NPLs and lower the probability of default by financial institutions. Ozili (2021b) showed that greater levels of financial inclusion would improve the cost efficiency of the financial sector in developing countries. Markose et al (2020) examined the economic viability of financial inclusion programs in India, and showed that higher financial inclusion programs, under the Pradhan Mantri Jan-Dhan Yojana (PMJDY) scheme, led to cost inefficiency among public sector banks.…”
Section: Determinants and Consequences Of Financial Inclusionmentioning
confidence: 99%
“…The positive impact is magnified when banking markets are less concentrated. Ozili (2021a), in a cross country analysis, examine whether high levels of financial inclusion are associated with greater financial risk in the banking sector. Financial risk was measured using the nonperforming loan ratio and cost to income ratio.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%